Mechanical Failure After Total En Bloc Spondylectomy and Salvage Surgery - Kwon, Shin Won; Chung, Chun Kee; Won, Young Il; Yuh, Woon Tak; Park, Sung Bae; Yang, Seung Heon; Lee, Chang Hyun; Rhee, John M.; Kim, Kyoung-Tae; Kim, Chi Heon (Neurospine, 2022)
Objective: Total en bloc spondylectomy (TES) is a curative surgical method for spinal tumors. After resecting the 3 spinal columns, reconstruction is of paramount importance. We present cases of mechanical failure and suggest strategies for salvage surgery.Methods: The medical records of 19 patients who underwent TES (9 for primary tumors and 10 for metastatic tumors) were retrospectively reviewed. Previously reported surgical techniques were used, and the surgical extent was 1 level in 16 patients and 2 levels in 3 patients. A titanium-based mesh-type interbody spacer filled with autologous and cadaveric bone was used for anterior support, and a pedicle screw/rod system was used for posterior support. Radiotherapy was performed in 11 patients (pre-TES, 5; post-TES, 6). They were followed up for 59 ± 38 months (range, 11–133 months).Results: During follow-up, 8 of 9 primary tumor patients (89%) and 5 of 10 metastatic tumor patients (50%) survived (mean survival time, 124 ± 8 months vs. 51 ± 13 months; p = 0.11). Mechanical failure occurred in 3 patients (33%) with primary tumors and 2 patients (20%) with metastatic tumors (p = 0.63). The mechanical failure-free time was 94.4 ± 14 months (primary tumors, 95 ± 18 months; metastatic tumors, 68 ± 16 months; p = 0.90). Revision surgery was performed in 4 of 5 patients, and bilateral broken rods were replaced with dual cobalt-chromium alloy rods. Repeated rod fractures occurred in 1 of 4 patients 2 years later, and the third operation (with multiple cobalt-chromium alloy rods) was successful for over 6 years.Conclusion: Considering the difficulty of reoperation and patients’ suffering, preemptive use of a multiple-rod system may be advisable.